Hypercytokinemia in COVID-19: Tear cytokine profile in hospitalized COVID-19 patients. (November 2020) - Burgos-Blasco, Barbara; Güemes-Villahoz, Noemi; Santiago, Jose Luis; Fernandez-Vigo, Jose Ignacio; Espino-Paisán, Laura; Sarriá, Beatriz; García-Feijoo, Julian; Martinez-de-la-Casa, Jose Maria
Abstract: The aim of this study is to analyze the concentrations of cytokines in tear of hospitalized COVID-19 patients compared to healthy controls. Tear samples were obtained from 41 healthy controls and 62 COVID-19 patients. Twenty-seven cytokines were assessed: interleukin (IL)-1b, IL-1RA, IL-2, IL-4, IL-5, IL-6, IL-7, IL-8, IL9, IL-10, IL-12, IL-13, IL-15, IL-17, eotaxin, fibroblast growth factor basic, granulocyte colony-stimulating factor (G-CSF), granulocyte-monocyte colony-stimulating factor (GM-CSF), interferon (IFN)-γ, interferon gamma-induced protein, monocyte chemo-attractant protein-1, macrophage inflammatory protein (MIP)-1a, MIP-1b, platelet-derived growth factor (PDGF), regulated on activation normal T cell expressed and secreted, tumor necrosis factor-α and vascular endothelial growth factor (VEGF). In tear samples of COVID-19 patients, an increase in IL-9, IL-15, G-CSF, GM-CSF, IFN-γ, PDGF and VEGF was observed, along with a decrease in eotaxin compared to the control group (p < 0.05). A poor correlation between IL-6 levels in tear and blood was found. IL-1RA and GM-CSF were significantly lower in severe patients and those who needed treatment targeting the immune system (p < 0.05). Tear cytokine levels corroborate the inflammatory nature of SARS-CoV-2. Highlights: Hyperinduction of proinflammatory cytokine plays an important role in the disease progression of patients infected with SARS-CoV-2. Tear levels of cytokines are increased in COVID-19 patients.